Heat flux sensing by anomalous Nernst effect in Fe–Al thin films on a flexible substrate. (9th March 2020) - Zhou, Weinan; Sakuraba, Yuya
Abstract: We performed a numerical analysis of the material parameters required for realizing a heat flux sensor exploiting the anomalous Nernst effect (ANE). The results showed the importance of high thermopower of ANE ( S ANE ) and small saturation magnetization. This motivated us to investigate the effect of Al substitution of Fe on ANE and found S ANE  = 3.4  μ V K −1 in Fe81 Al19 because of the dominant intrinsic mechanism. Using this material, we made a prototype ANE-based heat flux sensor on a thin flexible polyimide sheet and demonstrated accurate sensing with it. This study gives important information for enhancing sensor sensitivity.